PENGEMBANGAN E-MODUL MENGGUNAKAN FLIPBUILDER PADA KELAS V MATERI PERUBAHAN LINGKUNGAN - Azhari, Ridha Yuniar; Sandi Budiana; Tustiyana Windiyani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to develop, assess the feasibility and test the effectiveness of E-Module Media Using Flipbuilder in Class V Environmental Change Material, for class V students of Batu City Elementary School 06. This type of research is Research and Development (R&D) which refers to the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The resulting product is validated by 6 validators, namely media, language, and material experts, then tested on class V to evaluate their responses. The results of this study indicate that the response of students to this e-module media is very positive, with an assessment percentage of 83.55% and teachers show that the response of students to this e-module media is very positive, with an assessment percentage of 98% from media experts to 1 90% and from media experts to 2 88%, from language experts to 1 90% and language The implications of this study are expected to help teachers in learning and can improve the quality of e-module media in schools.